A community-based motivational personalised lifestyle intervention to reduce BMI in obese adolescents: results from the Healthy Eating and Lifestyle Programme (HELP) randomised controlled trial. Issue 8 (7th July 2017) - Christie, Deborah; Hudson, Lee Duncan; Kinra, Sanjay; Wong, Ian Chi Kei; Nazareth, Irwin; Cole, Tim J; Sovio, Ulla; Gregson, John; Kessel, Anthony S; Mathiot, Anne; Morris, Stephen; Panca, Monica; et al.
Abstract : Objective: Approximately 7% of children and young people aged 5–15 years in the UK have obesity at a level likely to be associated with comorbidities. The majority of multicomponent lifestyle programmes have limited applicability and generalisability for British adolescents. The Healthy Eating and Lifestyle Programme (HELP) was a specific adolescent-focused intervention, designed for obese 12 to 18-year-olds seeking help to manage their weight. Participants were randomised to the 12-session HELP intervention or standard care. The primary outcome was difference in mean body mass index (BMI) (kg/m 2 ) between groups at week 26 adjusted for baseline BMI, age and sex. Subjects: 174 subjects were randomised (87 in each arm), of whom 145 (83%) provided primary outcome data at week 26. Results: At week 26 there were no significant effects of the intervention on BMI (mean change in BMI 0.18 kg/m 2 for the intervention arm, 0.25 kg/m 2 for the control arm; adjusted difference between groups: −0.11 kg/m 2 (95% CI −0.62 to 0.40), p=0.7). At weeks 26 and 52 there were no significant differences between groups in any secondary outcomes. Conclusion: At minimum this study reinforces the need for higher level, structured interventions to tackle the growing public health burden of obesity in the UK and internationally. The HELP intervention was no more effective than a single educational session for reducing BMI in a community sample of obese adolescents. Further work is needed to understand how weight management programmes can be delivered effectively to young people from diverse and deprived backgrounds in which childhood obesity is common. The study has significant implications in terms of informing public health interventions to tackle childhood obesity. Trial registration number: ISRCTN: ISRCTN99840111 .